2019
DOI: 10.18231/j.ijfmts.2019.015
|View full text |Cite
|
Sign up to set email alerts
|

High voltage electrocution injury – A case report

Abstract: High voltage electrical injuries are comparatively unusual but show a high rate of mortality. A dead body of a truck driver who died while his truck trapped in overhead high-voltage cables was brought for post-mortem examination. The autopsy revealed typical electrocution injuries with first and second-degree burns, peeled off epidermis and flash burns around the body at different areas. The severity of electric shock varies between simple harmless shock to death. The passage of electric current through the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…10 Tyagi et al reported electric marks and joule burns are often seen only with low or medium voltage current and also both entry and exit marks are seen together only in 20% of cases. 7 In present series first case showed both entry and exit marks of electrocution but second case showed only entry wound of electrocution. Third case had a suspected electrocution wound.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…10 Tyagi et al reported electric marks and joule burns are often seen only with low or medium voltage current and also both entry and exit marks are seen together only in 20% of cases. 7 In present series first case showed both entry and exit marks of electrocution but second case showed only entry wound of electrocution. Third case had a suspected electrocution wound.…”
Section: Discussionmentioning
confidence: 47%
“…give less resistance than skin. 7 The effect of passage of an electrical current through the tissue can cause merely cause skin lesions to death. 1 For death occur due to electrocution, the human body must become a part of an active electrical circuit.…”
Section: Discussionmentioning
confidence: 99%
“…In India, electricity is divided into four types: Low voltage—up to 250 V, medium voltage—250 V to 650 V, high voltage—650 V to 33 kV, and extra high voltage—exceeding 33 kV [6]. In urban areas of India, the usual high‐voltage electric line carries around 7000–8000 V of electricity [7]. Electrocution with these high‐voltage wires is possible when these lines either break or fall to the ground, are touched, or come in contact with tall metallic objects such as a pole, ladder, or, as present in the reported case, a truck, with which an individual is in contact with [7].…”
Section: Discussionmentioning
confidence: 99%
“…In urban areas of India, the usual high‐voltage electric line carries around 7000–8000 V of electricity [7]. Electrocution with these high‐voltage wires is possible when these lines either break or fall to the ground, are touched, or come in contact with tall metallic objects such as a pole, ladder, or, as present in the reported case, a truck, with which an individual is in contact with [7]. If the electrical injury occurs to the individual due to close contact with such high‐voltage lines, it will result in superficial to deep burns involving a large surface area of the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation